HETERODOKSI DALAM KAJIAN AL-QUR’AN DAN TAFSIR DI MASA PEMBENTUKAN DAN PERTENGAHAN - Ahmad Ismatullah Basyari (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2025)
This article investigates the dynamics of heterodoxy within Qur’anic exegesis from the formative period of Islam through the medieval era, with particular emphasis on critical themes such as interpretive authority and authenticity, the plurality of religious sources, the agency of exegetes, and the role of ijtihād and scholarly dissent in shaping diverse theological discourses. Adopting a historical-hermeneutical approach, this study seeks to demonstrate that heterodoxy is not a deviation from orthodoxy, but rather a legitimate expression of Islam’s intellectual plurality. By analyzing select Qur’anic passages—specifically Q. 4:59, Q. 24:35, and Q. 3:7—the article elucidates how various schools of thought, including Sunni, Shi‘i, Mu‘tazilite, and Sufi traditions, have formulated divergent exegetical constructs grounded in distinct epistemological frameworks and socio-political contexts. It further argues that tafsir, as an intellectual discipline, is neither homogenous nor immutable; instead, it is inherently reflective, dialogical, and receptive to multiplicity. Heterodoxy emerges as a vital component in sustaining the dynamism and epistemic richness of the classical Islamic exegetical heritage. As a result, this study offers a conceptual contribution by advancing an alternative perspective that positions heterodoxy as essential to sustaining an exegetical tradition that remains inclusive, reflective, and dialogical. Artikel ini mengkaji dinamika heterodoksi dalam tafsir al-Qur’an dari masa pembentukan Islam hingga periode pertengahan, dengan menyoroti aspek-aspek kunci seperti otoritas dan otentisitas penafsiran, pluralitas sumber agama, agensi para mufassir, serta peran ijtihad dan perbedaan pendapat dalam membentuk ragam pemahaman keagamaan. Dengan menggunakan pendekatan historis-hermeneutik, studi ini ingin menunjukkan bahwa heterodoksi bukanlah bentuk penyimpangan dari ortodoksi, melainkan ekspresi sah dari keragaman intelektual Islam. Melalui analisis terhadap beberapa ayat al-Qur’an seperti QS 4:59, QS 24:35, dan QS 3:7, ditampilkan bagaimana berbagai mazhab—Sunni, Syi’ah, Muktazilah, dan Sufi—membangun konstruksi tafsir yang berbeda-beda sesuai dengan kerangka epistemologis dan konteks sosiopolitik masing-masing. Studi ini menegaskan bahwa tafsir sebagai disiplin ilmu tidak bersifat tunggal dan statis, melainkan reflektif, responsif, dan terbuka terhadap perbedaan. Oleh sebab itu, studi ini berkontribusi secara konseptual menawarkan perspektif alternatif yang memposisikan heterodoksi sebagai unsur vital dalam menjaga kelangsungan tradisi tafsir yang inklusif, reflektif, dan dialogis.